2020
DOI: 10.1177/0892705720904098
|View full text |Cite
|
Sign up to set email alerts
|

Physical and rheological properties of biodegradable poly(butylene succinate)/Alfa fiber composites

Abstract: Biodegradable poly(butylene succinate) (PBS)/Alfa fiber biocomposites were prepared through the compression molding method. Scanning electron microscopy images were acquired to assess the effects of reinforcement and homogenization of mixtures and to determine the characteristics of the microstructure. The rheological properties, melting, and crystallization behavior of neat PBS and its biocomposites were investigated. Regarding the thermal properties, it was observed that the presence of Alfa fibers facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Atualmente, há um grande crescimento na procura por materiais compósitos que utilizam fibras naturais, visto que são menos poluentes, em comparação com as fibras sintéticas (Marinho et al, 2018;Ferreira et al, 2019;Arabeche et al, 2020). O interesse no uso de fibras naturais como reforço de materiais compósitos está em constante ascensão, principalmente por causa das múltiplas vantagens associadas: são naturais, renováveis e atóxicas, são de fácil disponibilidade, apresentam baixa densidade, são biodegradáveis, apresentam custo baixo, alta rigidez e, ao mesmo tempo, são menos abrasivas (Jesus et al, 2019;Kotik, 2019;Padilha e Zard, 2010).…”
Section: Revisão Bibliográficaunclassified
“…Atualmente, há um grande crescimento na procura por materiais compósitos que utilizam fibras naturais, visto que são menos poluentes, em comparação com as fibras sintéticas (Marinho et al, 2018;Ferreira et al, 2019;Arabeche et al, 2020). O interesse no uso de fibras naturais como reforço de materiais compósitos está em constante ascensão, principalmente por causa das múltiplas vantagens associadas: são naturais, renováveis e atóxicas, são de fácil disponibilidade, apresentam baixa densidade, são biodegradáveis, apresentam custo baixo, alta rigidez e, ao mesmo tempo, são menos abrasivas (Jesus et al, 2019;Kotik, 2019;Padilha e Zard, 2010).…”
Section: Revisão Bibliográficaunclassified
“…where M p ¼ mass of pipe, L p ¼ length of pipe, r p ¼ density of pipe, t ¼ thickness of pipe, D i ¼ inside diameter of pipe, D O ¼ outside diameter of pipe. From the equation (18), it is obvious that the pipeline thickness has a significant impact on the weight of material. Consequently, for high-pressure gas transmission lines, designers may spend more money to use a high grade of pipe.…”
Section: Mass Of Cylinder Volume Of Cylinder ð16þmentioning
confidence: 99%
“…[15][16][17] Recently, researchers have examined various applications of natural fiber reinforced thermoplastics. For instance, physical and rheological properties of biodegradable composites, 18 application of eco-friendly composite materials in automotive industries, 19 non-structural facilities, 20 and biomedical, energy and sports. 21 Other recent studies on natural fibers and natural fiber reinforced plastics are well documented.…”
Section: Introductionmentioning
confidence: 99%
“…31 Some authors investigated that addition of cellulose fibers in biodegradable poly (butylene succinate) can enhance the thermal properties of the composite for engineering applications. 32 Kumar et al studied thermal and magnetic behavior of four different filaments, namely PLA with wood powder, PLA with polyvinyl chloride, PLA with Fe 3 O 4 , and virgin PLA, for multi-material 3D printing. The authors observed drastic improvement in mechanical properties with the addition of Fe 3 O 4 as compared with other reinforcements.…”
Section: Introductionmentioning
confidence: 99%
“…31 Some authors investigated that addition of cellulose fibers in biodegradable poly (butylene succinate) can enhance the thermal properties of the composite for engineering applications. 32…”
Section: Introductionmentioning
confidence: 99%